AN ANALYSIS OF STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT ( A STUDY AT THE EIGHTH GRADE OF SMP NEGERI 2 TAMBANGAN IN 2018/2019 ACADEMIC YEAR) - Asriani Hasibuan; Fitri Handayani (Journal MELT (Medium for English Language Teaching), 2019)
This study aims to know the student’s ability in writing narrative text in terms of content, organization, vocabulary, language use, and mechanics mastery at the eightth grade of SMP Negeri  2 Tambangan and to know why the students’ ability in writing narrative text in terms of content, organization, vocabulary, language use, and mechanics mastery are low at the eighth grade of SMP Negeri 2 Tambangan. The research was conducted by using mix method(quantitative and qualitative research) with 9 students as the informants. The documentation and interview were used in collecting the data. Based on data analysis, it could be found (a)the result of the from their ability in writing narrative text in terms of content, organization, vocabulary, language use, and mechanics still below the criteria minimum (KKM). The average all of the participants just on average 65 while the KKM value demanded that they must except to get the score on the average of criteria minimum at 75. and b) The result of the data finding showed that most of the students are unable in writing narrative text includes in content, organization, vocabulary, language use, and mechanics. It is proved from their score n writing narrative text are still below the KKM.  and c)Based on the writer’s interview to the 9 informants, most of students  think writing is difficult skill for them because they have limited understanding in vocabulary, grammar and tenses mastery.